Developing a smartphone-based training strategy for tobacco control in India: a formative study using consolidated framework for implementation research - Ghosh, Priyanka; Nagler, Eve M.; Warke, Smita; Pednekar, Mangesh S. (International Journal Of Community Medicine And Public Health, 2025)
Background: Tobacco free teachers-tobacco free society (TFT-TFS) is an evidence-based intervention (EBI) for making schools tobacco-free. Because scaling via in-person training has limitations, we conducted a formative study to develop a smartphone-based training strategy for TFT-TFS implementers in Madhya Pradesh (MP), India. Methods: We conducted key informant interviews (KIIs), focus group discussions (FGDs), and school observation visits in four districts of MP, India. We applied framework analysis guided by the consolidated framework for implementation research (CFIR). Results: Identified facilitators were from the domains: Innovation (a gamified Android app), outer setting (government campaigns, technological familiarity), inner setting (official permissions, WhatsApp groups, compliance with tobacco control guidelines, training feasibility), and individuals (smartphone access, implementers designated by principals). Barriers were from the outer setting domain, which included additional government tasks, smokeless tobacco use, alcohol consumption, pan masala advertisements by celebrities, and lack of statutory warnings on ‘over the top’ contents delivered over the internet. Conclusions: Understanding contextual factors is crucial for successful program implementation. The contribution of CFIR was instrumental in tool development, data analysis, training design, and TFT-TFS implementation.